Process of decolonization in Nābulyūn fī al-Azhar “Napoleon in Al-Azhar” - Abdulrahman Abdullah Al-Ma’amari; Noraini Md Yusof; Ravichandran Vengadasamy (Penerbit UKM, 2014)
This paper examines the decolonization process in Najib Al-Kailani‘s novel, Nābulyūn fī al-Azhar (Napoleon in Al-Azhar-1980). The study explores the ways the colonized react to the colonizers in order regain liberty, freedom, and sovereignty of their land. Decolonization is the reverse process of colonization by which colonies become independent of the colonizing country. Najib Al-Kailani (1931 – 1995) is an Egyptian novelist, poet, and critic. In his writings, he focuses on the colonial experiences that the Arabs and Muslims have faced throughout history. Al-Kailani here wrote a revisionist novel recounting the French invasion of Egypt in the eighteenth century (1798-1801) commanded by Napoleon Bonaparte (15 August 1769 – 5 May 1821), the general in Chief of what they called at that time ‗Armée d'Orient (English: Army of the Orient) and depicts the people‘s resistance and rebellion against the colonizer. The novel depicts the Egyptian resistance, against French subjugation and humiliation, and sacrifices for the sake of independence and dignity. The analysis of decolonization based on the events in the novel is executed by applying Frantz Fanon‘s theory of resistance and revolution which embodies three stages and steps of decolonization. These stages are: assimilation to the colonizer‘s culture, rediscovery of their own culture and identity, and finally the confrontation with the colonialists. Colonized people usually do not reach the confrontation stage with the colonizer unless they go through the first two stages; assimilation and rediscovery. The paper also discusses the impact of the violence experienced by both the colonizer and the colonized as a result of the confrontation.